The Challenges of Maharah Kitabah of ICBB Students in Yogyakarta - M. Syaddad Husein Al-Madani; Muhammad Syafii Tampubolon; Amrin Mustofa; Muhammad Ghufron (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
This study aims to identify and analyze the problems associated with the development of maharah al-kitabah in learning Arabic at Madrasah Aliyah. The research method used is descriptive qualitative research with data collection techniques through observation, interviews, and document analysis. The results of the study indicate that there are several problems encountered in the development of maharah al-kitabah in Madrasah Aliyah. First, limited resources and adequate learning materials are obstacles in developing students' maharah al-kitabah. The textbooks used do not support adequate writing practice, and the lack of access to varied reading materials also limits the development of students' writing skills. Second, the teacher's lack of understanding and skills in teaching maharah al-kitabah, especially in designing writing assignments that are varied and attract students' interest. Third, the low motivation and interest of students in learning to write Arabic, which can be caused by an unattractive learning approach and the low application of effective learning methods. To overcome this problem, a comprehensive effort is needed. First, it is necessary to develop more diverse and relevant learning resources and materials, including textbooks that better support writing practice. Second, the need for training and professional development for teachers in teaching maharah al-kitabah, including the use of innovative and effective learning methods. Third, it is necessary to increase student motivation and interest through interesting learning approaches, such as the use of information and communication technology and the application of interactive and participatory learning methods.